Vaccination, Health Policy, and the Challenge of Restoring Coverage in Argentina - Yedlin, Pablo (Revista del Hospital Italiano de Buenos Aires, 2026)
Vaccination, one of the most cost-effective public health interventions, is facing a concerning decline in coverage in Argentina and globally. This editorial examines its causes—beyond hesitancy—and highlights the need for comprehensive strategies to improve access, strengthen systems, and sustain public trust